2008
DOI: 10.1002/eji.200838333
|View full text |Cite
|
Sign up to set email alerts
|

B‐cell clonal diversification and gut‐lymph node trafficking in ulcerative colitis revealed using lineage tree analysis

Abstract: In studies of inflammatory bowel diseases (IBD), research has so far focused mainly on the role of T cells. Despite evidence suggesting that B cells and the production of autoantibodies may play a significant role in IBD pathogenesis, the role of B cells in gut inflammation has not yet been thoroughly investigated. In the present study we used the new approach of lineage tree analysis for studying immunoglobulin variable region gene diversification in B cells found in the inflamed intestinal tissue of two ulce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…This is in accordance with the previous findings where GC founder B cells were found to migrate between distinct secondary lymphoid tissues via the peripheral blood [40,41]. B-cell trafficking has been reported to occur between different follicles in follicular lymphoma [42][43][44] and between the gut and the associated lymph node in ulcerative colitis [45]. Circulating GC founder B cells were detected in the peripheral blood in primary Sjögren's syndrome and rheumatoid arthritis, although once seeded in the GC they no longer circulated [40].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with the previous findings where GC founder B cells were found to migrate between distinct secondary lymphoid tissues via the peripheral blood [40,41]. B-cell trafficking has been reported to occur between different follicles in follicular lymphoma [42][43][44] and between the gut and the associated lymph node in ulcerative colitis [45]. Circulating GC founder B cells were detected in the peripheral blood in primary Sjögren's syndrome and rheumatoid arthritis, although once seeded in the GC they no longer circulated [40].…”
supporting
confidence: 93%
“…Mutations were enumerated and analyzed using IgTree r [49] and additional programs incorporated into IgTree r that perform mutation targeting motif, aa replacement and R:S analyses [45], as explained in the following paragraphs. Thus, the results are subject to the tree structure as created by the IgTree r program.…”
Section: Ig Mutation Analysesmentioning
confidence: 99%
“…Mutations were counted per tree, as described in [32,43]. All trees were measured using our program MTree C , quantifying the graphical properties of the trees [20].…”
Section: Repertoire Diversity Lineage Tree and Mutation Analysesmentioning
confidence: 99%
“…Furthermore, the small amounts of DNA we could extract and the inability to isolate and clone specific B or plasma cells have necessitated a slightly nonstandard procedure in order to confirm there are no primer-induced biases (this paper) or that the results are equivalent to those obtained from, e.g. frozen samples [32]. However, limitations of the methodology would apply to all samples in our tissue analysis, so it is noteworthy that we observe agerelated differences between B-cell repertoires from old and young individuals.…”
mentioning
confidence: 99%
“…Previous studies demonstrated the usefulness of this method and resulted in new insights regarding differences in GC dynamics in aging or between different tissues [35]- [37],in autoimmune diseases [38], chronic inflammation [39], lymphomas [40], and chronic gastritis and gastric lymphomas [41]. This method was also used to determine clonal relationships of Ig genes from different tissues [39] [42].…”
Section: Introductionmentioning
confidence: 99%